Phenotypic and genotypic resistance profile of Salmonella Typhimurium to antimicrobials commonly used in poultry - Biffi,CP (2014)
Isolates of Salmonella sp (104) from poultry samples were isolated and serotyped where eleven were identified as Salmonella Typhimurium (ST). ST isolates were phenotypically tested by disk diffusion and minimum inhibitory concentration (MIC). Four genes related to enrofloxacin (GyrA, GyrB, ParC and ParE), two to gentamicin (AadA and AadB) and two to ceftiofur (BlaCMY-2 and AmpC) resistance were searched by PCR. Our results showed ST resistance to all three antibiotics tested (18.1% for ceftiofur, 45.4% for gentamicin, and 18.1% for enrofloxacin) according to the diffusion test. In the MIC test, the ST isolates showed higher levels of resistance (27.2% for ceftiofur, 54.5% for gentamicin, and 18.2% for enrofloxacin). Three resistance genes out of four searched genes for enrofloxacin were found in the ST isolates. Regarding gentamicin and ceftiofur, resistance genes were found mainly in samples with resistant phenotypic profile. Interestingly, some phenotypically-resistant strains did not present the resistance gene, which suggests an alternative route of resistance. Also, sensitive strains had the presence of the gene. It is possible to conclude that the ST isolates evaluated in this study have a multidrug resistance profile to the antibiotics routinely used in poultry production, and potential of greater levels of resistance in the near future.